“The Perfect Organism”: A Marxist Reading of Expendable Labor in Alien (1979) - Albar, Mahmud Arief (Talenta Publisher, 2025)
Ridley Scott’s critically acclaimed 1979 science fiction horror film Alien depicts the struggles of the crew of a spaceship named Nostromo against a murderous alien monster. The film has been interpreted through critical lenses such as feminism (Kuhn, 1990), psychoanalysis (Telotte, 2001), law (Crofts, 2021), and racism (Sobchak, 2001), but there is still room for other interpretations. This paper proposes a Marxist Cultural Studies reading of the film by conducting a close textual analysis of its narrative structure, character dialogue, production design, and cinematography to explore three core Marxist concepts: alienated labor, class conflict, and commodity fetishism. This is extended into an overview of the film’s contemporaneous socio-economic contexts of 1970s America (USA), such as power structure in the industrial economy, employment anxieties, corporate hegemony, in addition to the lasting effects of (Cold) War in the West. Findings show alienation of the Nostromo crew from: 1) their ‘product’ (the murderous alien lifeform they were directed to retrieve); 2) their productive activity (agreement to substandard terms driven only by wage compulsion); 3) their human potential (absence of purpose from labor); 4) other workers (distrust and expendability). The class conflict between the proletariat (the Nostromo crew) and the bourgeoisie (the faceless, inhumane corporation represented by the AI ‘Mother’ ship computer and by extension, the alien) structures the film’s narrative of exploitation and betrayal. And lastly, the alien monster can be interpreted as a fetishized commodity desired by the corporation for its potential value, completely outweighing the value of the crew’s lives. By paralleling these findings with the overview of 1970s America’s socio-economic issues in capitalism, such as distrust of authority and corporate hegemony, possible influences on the film’s themes can be seen. In conclusion, this Marxist critique reveals the film’s portrayal of expendable labor in ways that still resonate with modern audiences despite geopolitical space, facilitating a cross-cultural engagement on timeless and global social issues.